Urban Sprawl of Agricultural Areas in Amara City - Mohammed Arab Almusawi - Hanan Subhi Obaid ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
Urban sprawl against the agricultural lands is considered one of the most  important problems resulted from the swift housing growth in the developing states, for the agricultural lands are exposed to pressures and erosion as a result of this sprawl, urbanization process and weakness of deterrent laws. The Amara City had witnessed a noticed growth in averages of housing as a result of development requirements, population in the city rose from 272286 persons in 1997 to 577543 persons in 2020, and consequently caused settlement of numbers of inhabitants in the agricultural zones and changed plenty of land; from agricultural to housing and service ones, the matter that shared in the decrease of agricultural lands in Amara City, the thing that the occupied lands, preoccupied with housing and services amounted to 251 hectares during the five stages in which the city passed.